Tissue-Resident Macrophages in the Stria Vascularis - Ito, Taku; Kurata, Natsuko; Fukunaga, Yoko (Frontiers in Neurology, 2022)
Tissue-resident macrophages play an important role in clearance, development, and regulation of metabolism. They also function as sentinel immune cells, initiating inflammatory responses, clearing inflammatory debris, and maintaining homeostatic tissue environment. In the cochlea, the roles of tissue-resident macrophages include maintaining steady-state tissues, immunological defense, and repairing pathological conditions associated with noise, ototoxic drugs, aging, and various pathogens. Perivascular macrophages (PVMs) are a unique subset of tissue-resident macrophages that are closely associated with blood vessels and have unique expression markers in certain tissues. PVMs are found in the inner ear, brain, skin, liver, and retina. The origin of PVMs in the inner ear is unclear, but they are already present during embryonic development. PVMs are members of the blood labyrinth barrier and regulate blood vessel permeability in the stria vascularis, which lies on the lateral wall of the cochlear duct and is crucial for endocochlear potential formation. The cytoplasm of strial PVMs can contain pigment granules that increase in number with age. Strial PVMs are activated by the loss of Slc26a4 in the cochleae, and they subsequently phagocytose aggregated pigment granules and possibly degenerated intermediate cells. This review summarizes the current knowledge of characteristic features and proposed roles of PVMs in the stria vascularis. We also address macrophage activation and involvement of pigment granules with the loss of Slc26a4 in the cochleae.